Analisis Penerapan Akad Wadi’ah dalam Inovasi Keuangan Pesantren Melalui E-Santri (Studi Kasus Pondok Pesantren Madrasatul Qur’an Tebuireng) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This research is motivated by the problem of cash financial management in Islamic boarding schools, which still poses security risks, potential recording errors, and limited transparency in transaction reporting. These conditions prompted the Madrasatul Qur'an (MQ) Tebuireng Islamic Boarding School to develop an innovative digital financial system in the form of E-Santri as an alternative for integrated non-cash transaction management. This study aims to analyze the implementation mechanism of E-Santri and assess the suitability of implementing wadi'ah contracts in the system from a sharia economic law perspective. The research method used is empirical legal research (empirical juridical) with a case study approach. Data were collected through system observation, interviews with students' managers and guardians, and financial report documentation, then analyzed descriptively and analytically. The results show that E-Santri is able to integrate digital technology with sharia microfinance services through BPRS Lantabur, thereby increasing transaction security, minimizing human error, and providing real-time financial reports. From a sharia perspective, this system is in accordance with the principles of wadi'ah yad amanah because funds remain intact without deductions for commercial costs and can be fully returned to their owners. Thus, the implementation of E-Santri is considered effective and in line with the principles of Islamic economic law in managing Islamic boarding school finances.